Acute Starvation Protects Mice Against Listeria monocytogenes - Wing, Edward J. (1980)
We investigated the effect of starvation on the course of Listeria monocytogenes infections in mice. Mice starved for 24, 48, or 72 h and then inoculated with a lethal dose of L. monocytogenes showed significantly less mortality than mice not starved (i.e., fed mice). The protective effect of 48 or 72 h of starvation began immediately after the starvation period and persisted for at least 48 h. Starved, infected mice had significantly fewer L. monocytogenes cells in their spleens 2, 3, and 4 days after infection than did fed mice. Neither changes in T-lymphocyte function nor serum factors appeared to be responsible for the protective effect. Delayed hypersensitivity responses to L. monocytogenes antigen were smaller in starved mice than in fed mice. Adoptive transfer of spleen cells from nonimmune starved mice did not protect against L. monocytogenes. Additional studies indicated that the serum of starved mice did not inhibit multiplication of L. monocytogenes in vitro, nor was it able to transfer protection against L. monocytogenes to normal mice. In contrast, peritoneal macrophages from starved mice inhibited deoxyribonucleic acid synthesis of P815 tumor cells compared with macrophages from control mice. Therefore, the resistance of starved mice to L. monocytogenes is most likely due to nonspecific factors, one of which may be activation of macrophages.